2022
DOI: 10.1186/s13071-022-05322-7
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of Lucilia sericata larval excretion/secretion products on Leishmania major under in vitro and in vivo conditions

Abstract: Background Leishmaniasis is a neglected infectious disease caused by protozoa of the genus Leishmania. The disease generally manifests as characteristic skin lesions which require lengthy treatment with antimonial drugs that are often associated with adverse side effects. Therefore, a number of studies have focused on natural compounds as promising drugs for its treatment. This study aimed to evaluate the effects of larval excretion/secretion products (ES) of Lucilia sericata in crude and fract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
(71 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, significant decreases in parasite loads and survival indexes were observed in treated groups compared to the untreated control ( P = 0.05), which was consistent with findings of Rahimi et al [ 37 ]. Our study confirmed the result of Sherafati et al that honey acts as a synergist with ES products [ 30 ]. Indeed, leishmanicidal effects of larval ES products in combination with honey to intracellular amastigotes provide a promising basis for in vivo experimentation in future.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, significant decreases in parasite loads and survival indexes were observed in treated groups compared to the untreated control ( P = 0.05), which was consistent with findings of Rahimi et al [ 37 ]. Our study confirmed the result of Sherafati et al that honey acts as a synergist with ES products [ 30 ]. Indeed, leishmanicidal effects of larval ES products in combination with honey to intracellular amastigotes provide a promising basis for in vivo experimentation in future.…”
Section: Discussionsupporting
confidence: 92%
“…To obtain larval ES, about 100 stage II and III larvae of L . sericata were selected from previously established colonies and disinfected as described by Cruz-Saavedra et al [ 29 , 30 ]. The ES was collected by centrifugation at 4000 g for 10 minutes [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation